Análise do padrão facial de pacientes Classe II em crescimento após o tratamento com aparelho de Thurow modificado - Monteiro, Aline Levi Baratta (2022)
In the treatment of Class II/1 malocclusion, both the correct diagnosis and the monitoring of the vertical control can be associated with desirable results. Several cephalometric measurements, angular or linear, are very valuable tools in this process. In an attempt to achieve favorable changes or, at least, maintenance of the vertical dimension, patients in the growth phase with maxillary protrusion have been treated with headgear; including the modified Thurow appliance (MTA). In order to explore this issue, the present research was divided into two parts. In the first one, a retrospective study was carried out to verify whether the use of different cephalometric measurements would influence the determination of the facial pattern. It was used a sample with pre (T1) and post-treatment (T2) lateral cephalograms of 27 individuals in the growth phase, with Class II/1 malocclusion, treated with MTA. After scanning the images, the facial patterns of these patients were established based on measurements from four different cephalometric analyses. Then, the results indicated by each analysis were compared between T1 and T2 using Pearson's chi-square test or Fisher's exact test and the agreement between the analyses was verified using the McNemar test and the Kappa method (k). It was observed that only one measure showed significant variations between T1 and T2 (p = 0,026), while when each method was evaluated in relation to the others, the vast majority showed a statistically significant difference (p < 0,001), in addition to correlations non-existent or minimal (k < 0 or 0 < k ≤ 0,20, respectively). It was concluded that the facial pattern of Class II/1 patients was evaluated in a non-homogeneous way, when using different cephalometric measurements, especially those that use only parameters of the anterior or posterior region. In the second part of the research, a systematic review was carried out in order to investigate the dentoskeletal effects of the TM in the treatment of the Class II/1 hyperdivergent patients in the growth phase. After selecting the studies and applying the eligibility criteria, 7 articles were included in the study, for data extraction and analysis. The literature evaluated revealed that the use of this device provides: (1) inhibition of the vertical development of the maxilla, mainly in the posterior region, with counterclockwise rotation of the mandible; (2) maintenance of the facial pattern; (3) significant reduction in the overjet; (4) improvement of the interincisal relationship and (5) establishment of the Class I molar relationship. However, additional clinical trials of better quality are needed to elucidate the real effects of this therapy on the growth pattern of these patients.